City Lodge Hotel Group : redefining segments and brands - Saini, Yvonne (SAGE Knowledge. Cases., 2017)
In 1985, the market regarded Hans Enderle as foolhardy when he resigned from the helm of one of South Africas leading hotel chains to launch a new concept in short-stay accommodation. However, by 1990, his City Lodge select service hotel concept boasted seven hotels, with 1 000 rooms. By 2015, the hotel groups portfolio had risen to 55 hotels and annual turnover had reached more than R1 billion. However, growing competition and increasing customisation within the hotel industry meant that in early November 2015, current group chief executive (CE), Clifford Ross, had concerns about the clarity of the groups brand and whether it was losing its competitive edge.